2022
DOI: 10.1021/acsphotonics.2c00249
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Strain-Decoupled Fluorescent Optical Fiber Sensor for Body Temperature and Movement Monitoring

Abstract: A stretchable fluorescent optical fiber provides a flexible platform for wearable functional devices due to its stretchability and immunity to electromagnetic interference. However, for wearable applications, stretchable fiber sensors suffer from severe body movement-induced strain interference. Here, we report a stretchable optical sensor with strain-decoupling ability. The stretchable core-clad structured optical fiber is prepared with fluorescent nanoparticles and silicone-based elastomers that enable both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…They demonstrated that despite the scalability of graphene inks, graphene grown via chemical vapor deposition is more suitable for temperature sensors and concluded that these sensors have a potential application in continuous measurement of the human body temperature while being integrated into garments or of the ambient temperature while being integrated into upholstery. Chen et al [ 161 ] obtained temperature-sensitive fluorescent nanoparticle-doped stretchable fluorescent optical fiber that exhibits stable temperature-sensing in the range of −10 to 60 °C with an uncertainty as low as ±0.23 °C and a relative sensitivity of 1.3% °C –1 , even when it is subjected to large strain up to 40%. They demonstrated sensor-integrated wearable masks and gloves, which can simultaneously measure physiological thermal changes and the movement of the wrist joint.…”
Section: Smart Textiles For Monitoring and Sensing As Part Of The Tel...mentioning
confidence: 99%
“…They demonstrated that despite the scalability of graphene inks, graphene grown via chemical vapor deposition is more suitable for temperature sensors and concluded that these sensors have a potential application in continuous measurement of the human body temperature while being integrated into garments or of the ambient temperature while being integrated into upholstery. Chen et al [ 161 ] obtained temperature-sensitive fluorescent nanoparticle-doped stretchable fluorescent optical fiber that exhibits stable temperature-sensing in the range of −10 to 60 °C with an uncertainty as low as ±0.23 °C and a relative sensitivity of 1.3% °C –1 , even when it is subjected to large strain up to 40%. They demonstrated sensor-integrated wearable masks and gloves, which can simultaneously measure physiological thermal changes and the movement of the wrist joint.…”
Section: Smart Textiles For Monitoring and Sensing As Part Of The Tel...mentioning
confidence: 99%
“…Besides, the upconversion fluorescence excitation and collection are performed with a bulky free-space optical systems that is unfavorable in flexible temperature detection. A promising approach is to incorporate the temperature-sensitive upconversion materials into optical fibers, especially the flexible polymers (e.g., hydrogels and elastomers). Flexible optical fibers that were fabricated from a transparent matrix exhibit excellent light-guidance performance and flexibility, which holds great promise for developing a wearable platform for temperature sensing. In this work, a biocompatible and flexible optical temperature sensor was developed by doping the hybrids of UCNPs and plasmonic semiconductor W 18 O 49 (UCNPs/WO) in flexible poly­(lactic acid) (PLA)-based optical fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, over the past decade, chemical-based information encryption strategies are attracting increasing attention for meeting the challenge of information recording and encryption. Among the relative encryption materials, fluorescent materials have aroused extensive attention due to the intelligence capability to sense, store, analyze, and respond to the external stimuli (solvents, ions, light, molecules, mechanical force, etc. ), making these materials have potential applications in sensors, bioimaging, displays, optical recording, and information security. Meanwhile, fluorescence response endows the luminescent materials with intelligence, which can be displayed by an optical signal output accompanying with the obvious luminescence change such as quenching, enhancement, and emission peak shift toward the external stimuli. Using the fluorescence response mechanism of fluorescent materials toward the external stimuli, chemical-based information security can realize the information storage, encryption, decryption, and anticounterfeiting benefiting from the superior selectivity and unique fluorescence response and therefore strengthen the information security level. In recent years, smart hydrogels, as one of the representative fluorescent materials, are also employed to improve the information security.…”
Section: Introductionmentioning
confidence: 99%